Comparative study of nanoadditives TiO2, CNT, Al2O3, CuO and CeO2 on reduction of diesel engine emission operating on hydrogen fuel blends. (15th February 2020) - Manigandan, S.; Sarweswaran, R.; Booma Devi, P.; Sohret, Yasin; Kondratiev, Andrii; Venkatesh, S.; Rakesh Vimal, M.; Jensin Joshua, J.
Highlights: Dual fuelled hydrogen powered diesel engine studied with nano additives. CNT is least stable than TiO2 and Al2 O3 . TiO2 and CNT shows profound reduction in BSFC and improved BTE. Reduction in the formation of unburned hydrocarbons. NOx reduced from 450 to 350 ppm of biodiesel blended with CNT nanoadditive. Abstract: In this study, the impact of nanoparticles and hydrogen blends on combustion, performance and emission characteristics of modified dual fuel engine was investigated. The nanoparticles TiO2, CNT, Al2 O3, CuO and CeO2 are dispersed at a fraction of 100 ppm with 20% hydrogen to form blends HT100, HCT100, HA100, HCE100 and HC100 respectively. The nanoparticles are agitated using ultrasonication process to increase the stability of blends. All blends are tested at 1800 rpm for different engine load varying from 0%, 25%, 50%, 75% and 100% respectively. The addition of nanoparticles does not show a substantial effect on density, kinematic viscosity and flash point and cetane number. Further, the nanoparticles CNT and TiO2 showed a better stability with 30% and 21% absorption rate at 240 h sedimentation time. All tested nanoparticles showed a profound change in the maximum cylinder pressure rates in comparison to neat diesel. Besides, the addition of CeO2 and Al2 O3 improves the brake thermal efficiency by 4.3% and 2.5%. Meanwhile no significant change in brake specific fuel consumption is recorded for CeO2 . The nanoparticles CNT and TiO2 reports 23% and 22% reduced BSFC than other blends. The results of exhaust emission showed addition of hydrogen and nanoparticles decreases the emission of carbon monoxide, carbon dioxide and hydrocarbon significantly. However, regarding NOx emission only CNT showed a profound decrease in NOx than other blends. From the results it is evident that, addition of nanoparticles and hydrogen on neat diesel improves the combustion characteristics and engine performance with reduced exhaust gas emission.